2006
DOI: 10.1002/anie.200504486
|View full text |Cite
|
Sign up to set email alerts
|

Relative Strengths of the OH⋅⋅⋅Cl and OH⋅⋅⋅F Hydrogen Bonds

Abstract: Hydrogen bonding involves many scientific areas and is invoked to explain the energetic and structural features of inorganic, organic, and biological chemical systems. [1,2] Herein, we show that a water molecule in a solvent-free environment prefers to form a hydrogen bond with a Cl atom rather than with a F atom. For this purpose, several isotopologues of chlorofluoromethane/water were studied by molecular-beam Fourier transform rotational spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 36 publications
3
64
0
Order By: Relevance
“…[11] and H 2 OÀCH 2 ClF; [12] namely, H 2 CO and H 2 O are linked to the partner molecule through two weak hydrogen bonds and undergo internal rotation around their C 2 symmetry axes. The corresponding tunneling splitting of H 2 CO is larger than that of H 2 O, thus indicating that the V 2 barrier to internal rotation is lower for H 2 CO.…”
Section: Introductionmentioning
confidence: 99%
“…[11] and H 2 OÀCH 2 ClF; [12] namely, H 2 CO and H 2 O are linked to the partner molecule through two weak hydrogen bonds and undergo internal rotation around their C 2 symmetry axes. The corresponding tunneling splitting of H 2 CO is larger than that of H 2 O, thus indicating that the V 2 barrier to internal rotation is lower for H 2 CO.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the OÀH···Cl hydrogen bond is slightly preferred to the O À H···F one, [8] but their energies have been estimated to be rather small (4-5 kJ mol À1 ). [8] These energy values are similar to those estimated for weak C À H···O, [9] C À H···F [10] or CÀH···p [11] interactions, which are classified as weak [12] or blue-shifted hydrogen bonds. [1] The simplest molecules containing halogen atoms (F 2 and ClF) react with water.…”
mentioning
confidence: 99%
“…The hydrogen bonding of water with halogens (O À H···X) is somewhat elusive. The O À H···F and O À H···Cl bonds have been characterized through analysis of the rotational spectra of the complexes of water with Freon-32 (difluoromethane) [7] and Freon-31 (chlorofluoromethane), [8] respectively. It has been shown that the OÀH···Cl hydrogen bond is slightly preferred to the O À H···F one, [8] but their energies have been estimated to be rather small (4-5 kJ mol À1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] When both Cl and F atoms are present in a freon molecule, sometimes the OH···Cl linkage is favorite, [11b] but the OH···F one is preferred in other cases.…”
mentioning
confidence: 99%